2019
DOI: 10.1159/000498910
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Nontuberculous Mycobacteria in Kuwait: Rapid Identification and Differentiation of <b><i>Mycobacterium</i></b> Species by Multiplex PCR, INNO-LiPA Mycobacteria v2 Assay and PCR Sequencing of rDNA

Abstract: Objective: Nontuberculous mycobacteria (NTM) often cause disease that is clinically indistinguishable from tuberculosis. Specific identification is important as treatment varies according to Mycobacterium species causing the infection. This study used multiplex PCR (mPCR) assay for rapid differentiation of mycobacterial growth indicator tube 960 system (MGIT) cultures as Mycobacterium tuberculosis (MTB) or NTM together with INNO LiPA Mycobacteria v2 assay (LiPA) and/or PCR sequencing of rDNA for species-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Despite these measures, previous studies have shown that >80% of M . tuberculosis isolates and >90% of MDR-TB strains are isolated from expatriate TB patients in Kuwait [ 4 , 26 , 33 ]. Fingerprinting of M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these measures, previous studies have shown that >80% of M . tuberculosis isolates and >90% of MDR-TB strains are isolated from expatriate TB patients in Kuwait [ 4 , 26 , 33 ]. Fingerprinting of M .…”
Section: Discussionmentioning
confidence: 99%
“…It is also pertinent to mention here that all expatriates entering Kuwait are screened and residence visa is granted only to individuals with no evidence of active TB disease. Despite these measures, previous studies have shown that >80% of M. tuberculosis isolates and >90% of MDR-TB strains are isolated from expatriate TB patients in Kuwait [4,26,33]. Fingerprinting of M. tuberculosis isolates (n = 256) collected from 256 TB patients over a six-month period (October 2017 to March 2018) was performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of laboratory methods to identify these species was significant, and it plays a vital role in this https://doi.org/10.1017/S0950268822000899 Published online by Cambridge University Press rising tendency [6]. In this study, changing the test from a probe assay to a PCR-fluorescence probe allowed the identification of 4 more species/subspecies in 2019 (10 vs 6).…”
Section: Discussionmentioning
confidence: 88%
“…EPTB accounts for ∼15% of all TB cases worldwide with the maximum prevalence of 24% reported from the WHO Eastern Mediterranean Region [1,7]. The Eastern Mediterranean Region includes Kuwait, an Arabian Gulf country where ∼95% of mycobacterial infections are caused by M. tuberculosis [8]. Kuwait has a low incidence of TB (∼24 cases per 100,000 population), high (44%) prevalence of EPTB, and a low (∼1.1%) incidence of MDR-TB [7,9].…”
Section: Introductionmentioning
confidence: 99%